2021
DOI: 10.3390/jsan10010006
|View full text |Cite
|
Sign up to set email alerts
|

A Green Routing Protocol with Wireless Power Transfer for Internet of Things

Abstract: The usually constrained resources and lossy links scenarios of Internet of Things (IoT) applications require specific protocol suite, as the IPv6 Routing Protocol for Low-Power and Lossy Networks (RPL). Due to its flexibility, RPL can support efficiently vertical applications such as environmental monitoring, smart city and Industry 4.0. In this paper, we propose a new Objective Function (OF) for RPL based on a composite metric considering jointly the residual energy of a node (parent) together with the energy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 36 publications
(56 reference statements)
0
8
0
Order By: Relevance
“…Moreover, these works assumed a constant replenishment rate for all nodes, which makes them unsuitable to deal with the stochastic characteristics of the ambient energy sources. Motivated by the significant benefits of WPT to wirelessly charge devices' batteries through a dedicated and fully controlled RF power source, the authors of [16] studied the use of WPT technology in low-power and lossy network (RPL) model, where they proposed a new objective function for RPL, which jointly considers the energy consumption of intermediate nodes and the amount of recharging energy available from the received power of a child node. Simulation results demonstrated that the proposed algorithm efficiently minimizes the energy loss and extends the network lifetime by selecting the most efficient path via the sink.…”
Section: A Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, these works assumed a constant replenishment rate for all nodes, which makes them unsuitable to deal with the stochastic characteristics of the ambient energy sources. Motivated by the significant benefits of WPT to wirelessly charge devices' batteries through a dedicated and fully controlled RF power source, the authors of [16] studied the use of WPT technology in low-power and lossy network (RPL) model, where they proposed a new objective function for RPL, which jointly considers the energy consumption of intermediate nodes and the amount of recharging energy available from the received power of a child node. Simulation results demonstrated that the proposed algorithm efficiently minimizes the energy loss and extends the network lifetime by selecting the most efficient path via the sink.…”
Section: A Related Workmentioning
confidence: 99%
“…In this paper, we assume that the battery parameters remain constant over time. The PDF of battery recharging time can be obtained using (11) through the Jacobian approach using (16). Hence, the PDF of the BRT can be written as follows…”
Section: ) Statistical Characterization Of the Battery Recharging Timementioning
confidence: 99%
“…Authors in [16] suggested a unique method for RPL protocol trying to develop the IoT network lifetime. The suggested method combined the consumed and recharged energy to choose the most suitable route to send data information.…”
Section: Related Workmentioning
confidence: 99%
“…In Varga et al, 20 the author proposed a stack of network protocols specially meant for energy harvesting enabled WSNs, the author presented results was the power consumption using his proposed stack of protocols compared to the network power consumption when using standard protocols. Similarly, Chiti et al, 21 Sarwar et al, 22 and Liu et al 23 focused on proposing greener RPL protocol, for which nodes power consumption is more efficient and thus can be suitable for autonomous and EH enabled WSNs. Other works which may be considered relevant to ours are the studies by Liu et al, Lu et al, and Clerckx et al, [24][25][26] which all proposed RF energy harvesting methods, this may be relevant since WSNs' nodes do have an RF module which is the module having the highest power consumption.…”
Section: Related Workmentioning
confidence: 99%